Hemorrhagic Transformation in Patients With Acute Ischemic Stroke and Atrial Fibrillation: Time to Initiation of Oral Anticoagulant Therapy and Outcomes. Issue 22 (20th November 2018) - Paciaroni, Maurizio; Bandini, Fabio; Agnelli, Giancarlo; Tsivgoulis, Georgios; Yaghi, Shadi; Furie, Karen L.; Tadi, Prasanna; Becattini, Cecilia; Zedde, Marialuisa; Abdul‐Rahim, Azmil H.; Lees, Kennedy R.; Alberti, Andrea; et al.
Abstract : Background: In patients with acute ischemic stroke and atrial fibrillation, early anticoagulation prevents ischemic recurrence but with the risk of hemorrhagic transformation (HT). The aims of this study were to evaluate in consecutive patients with acute stroke and atrial fibrillation (1) the incidence of early HT, (2) the time to initiation of anticoagulation in patients with HT, (3) the association of HT with ischemic recurrences, and (4) the association of HT with clinical outcome at 90 days. Methods and Results: HT was diagnosed by a second brain computed tomographic scan performed 24 to 72 hours after stroke onset. The incidence of ischemic recurrences as well as mortality or disability (modified Rankin Scale scores >2) were evaluated at 90 days. Ischemic recurrences were the composite of ischemic stroke, transient ischemic attack, or systemic embolism. Among the 2183 patients included in the study, 241 (11.0%) had HT. Patients with and without HT initiated anticoagulant therapy after a mean 23.3 and 11.6 days, respectively, from index stroke. At 90 days, 4.6% (95% confidence interval, 2.3–8.0) of the patients with HT had ischemic recurrences compared with 4.9% (95% confidence interval, 4.0–6.0) of those without HT; 53.1% of patients with HT were deceased or disabled compared with 35.8% of those without HT. On multivariable analysis, HT was associated with mortality or disability (odds ratio, 1.71; 95% confidence interval, 1.24–2.35). Conclusions: In patients with HT, anticoagulation was initiated about 12 days later than patients without HT. This delay was not associated with increased detection of ischemic recurrence. HT was associated with increased mortality or disability.